2014
DOI: 10.3758/s13414-014-0813-1
|View full text |Cite
|
Sign up to set email alerts
|

Deviating to the right: Using eyetracking to study the role of attention in navigation asymmetries

Abstract: The ability to navigate accurately through the environment and avoid obstacles is essential for effective interactions with the environment. It is therefore surprising that systematic rightward errors are observed when neurologically intact participants navigate through doorways-most likely due to the operation of biases in spatial attention. These rightward errors may arise due to the operation of an extinction-like process, whereby participants overattend to the left doorpost and collide with the right one. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 77 publications
(105 reference statements)
1
21
0
Order By: Relevance
“…For instance, people tend to pass through doorways to the right of true centre [ 23 ], and doorframe collisions are more likely to occur on the right side of the body than the left [ 24 ]. Furthermore, right-sided bumping also occurs when navigating doorways using electric wheelchairs, scooters and remote-controlled cars [ 25 27 ]). It is possible that the dimensions of left hemispace are perceptually overestimated and compensated for by shifting behaviourally rightward as a result.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, people tend to pass through doorways to the right of true centre [ 23 ], and doorframe collisions are more likely to occur on the right side of the body than the left [ 24 ]. Furthermore, right-sided bumping also occurs when navigating doorways using electric wheelchairs, scooters and remote-controlled cars [ 25 27 ]). It is possible that the dimensions of left hemispace are perceptually overestimated and compensated for by shifting behaviourally rightward as a result.…”
Section: Introductionmentioning
confidence: 99%
“…() when walking. Furthermore, the literature available on navigation errors and related phenomena in healthy population (determined as direction of attention/gaze, ambulatory and wheelchair tasks, simulators, right‐ or left‐side traffic), discussed recently by Robertson, Forte and Nicholls (), is puzzling and highly equivocal with both right‐ and left‐side biases related to both neglect, pseudoneclect, bisection‐bias, extinction etc. Recent study by Benwell, Harvey, Cardner and Thut (2014) demonstrates the “shift of visuospatial attention vector” to the right as a function of aging in a landmark task, which indeed may come close to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, it has been reported previously that patients with hemispatial neglect, who demonstrate the pathological bias of spatial perception and attention to the right hemispace, have a bias for left-side collisions (Punt, Kitadono, Hulleman, Humphreys & Riddoch, 2008;Turton, Dewar, Lievesley, O'Leary, Gabb & Gilchrist, 2009) when navigating a wheelchair, but to the right by the same subjects in the study by Turton et al (2009) when walking. Furthermore, the literature available on navigation errors and related phenomena in healthy population (determined as direction of attention/gaze, ambulatory and wheelchair tasks, simulators, right-or left-side traffic), discussed recently by Robertson, Forte and Nicholls (2015), is puzzling and highly equivocal with both right-and left-side biases related to both neglect, pseudoneclect, bisection-bias, extinction etc. Recent study by Benwell, Harvey, Cardner and Thut (2014) demonstrates the "shift of visuospatial attention vector" to the right as a function of aging in a landmark task, which indeed may come close to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Across six experiments, consistent rightward biases were observed, leading the authors to conclude that a rightward bisection of the doorway in far space provided a good explanation of their findings. This explanation is further strengthened by research showing that participants look to the right when navigating an aperture and mark the centre to the right of true centre on these trials (Robertson et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…This attentional bias is known as pseudoneglect (Bowers & Heilman, 1980;Jewell & McCourt, 2000;Learmonth, Gallagher, Gibson, Thut, & Harvey, 2015). Although these asymmetries were initially recorded on pencil-and-paper and computerised tasks in the laboratory, more recent research has demonstrated that these asymmetries also extend to real-world behaviours, such as sporting performance (see for a review), driving (Friedrich, Elias, & Hunter, 2017;Learmonth, Märker, McBride, Pellinen, & Harvey, 2018), and navigation (Nicholls, Loftus, Mayer, & Mattingley, 2007;Nicholls et al, 2010;Robertson, Forte, & Nicholls, 2015;Thomas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%